El libro por venir. Acerca del texto virtual y su lectura matérica - Santana Pérez, Sandra (Escritura e Imagen, 2006)
The increasing use of electronic media for the transmission and creation of texts, along with the resulting transformations in the way we understand the acts of reading and writing, demand our reflection about the limits and possibilities of the concept of “book”, as something detached from the paper and from its condition as a finished and cohesive work. This article proposes a brief approach, based on ideas from Derrida, Blanchot and Mallarmé, to three artworks (“La Pluie” by Marcel Broodthaers, “Open Book” by Vito Acconci and “Sighs trapped by liars” by the Art & Language group) that present new perspectives on these problems from the field of conceptual art.